An Overview of Vasculogenic Mimicry in Breast Cancer - Andonegui-Elguera, Marco A.; Alfaro-Mora, Yair; Cáceres-Gutiérrez, Rodrigo; Caro-Sánchez, Claudia Haydee Sarai; Herrera, Luis A.; Díaz-Chávez, José (Frontiers in Oncology, 2020)
Vasculogenic mimicry (VM) is the formation of vascular channels lacking endothelial cells. These channels are lined by tumor cells with cancer stem cell features, positive for periodic acid-Schiff, and negative for CD31 staining. The term VM was introduced by Maniotis et al. (1), who reported this phenomenon in highly aggressive uveal melanomas; since then, VM has been associated with poor prognosis, tumor aggressiveness, metastasis, and drug resistance in several tumors, including breast cancer. It is proposed that VM and angiogenesis (the de novo formation of blood vessels from the established vasculature by endothelial cells, which is observed in several tumors) rely on some common mechanisms. Furthermore, it is also suggested that VM could constitute a means to circumvent anti-angiogenic treatment in cancer. Therefore, it is important to determinant the factors that dictate the onset of VM. In this review, we describe the current understanding of VM formation in breast cancer, including specific signaling pathways, and cancer stem cells. In addition, we discuss the clinical significance of VM in prognosis and new opportunities of VM as a target for breast cancer therapy.